Morphological changes in the membranogenic pulmonary edema after replacement surfactant therapy administration. - Novikov, N. Yu. (Морфологія / Morphologia / Morfologìâ, 2012)
The purpose of this study was to establish the morphologic changes in development of membranogenic pulmonary edema without and after administration of replacement surfactant therapy. The object of study are morphologic changes in the respiratory part of lungs after administration of replacement surfactant therapy by medication "Suzakrin." Study of hematoxylin and eosin stained sections revealed that the administration of replaced surfactant therapy had led to reducing the manifestations of the inflammation’s vascular component, to decreasing the frequency of hyaline membranes’ formation and also to proliferation of pneumocyte. In addition it was found that 30% of patients with syndrome of an acute lung injury, who died after 14 days of disease, had morphologic signs of exudative phase of an acute respiratory distress syndrome. The administration of replacement surfactant therapy in patients with an acute lung injury syndrome can influence on the regeneration processes in the lungs’ respiratory part and morphogenesis of pneumofibrosis.